The Meritocratic Mystique and Mathematical Mediocrity in Hard-to-Staff Schools: A Critique of the Best and Brightest Teacher Agenda. (September 2020) - Brantlinger, Andrew
This article presents a critique of a teacher quality agenda promoted by a network of elitiste organizations in the United States. Network leaders posit that gaps in teacher quality cause achievement gaps. Their solution is to incentivize the graduates of the nation's most selective colleges to teach in hard-to-staff schools. Summarizing prior results from secondary mathematics, this article argues that selective college graduates do not make particularly effective teachers and, given their high rates of attrition, do more harm than good. It concludes with the recommendation to invest instead in the development of community teachers to teach core subjects like mathematics.